From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.